Secretarial practice and office management today - Edun, Babatunde A.; Ajetunmobi, S. S. (Ibadan, Nigeria : University Press Limited, 1986)
The book examines the principles and techniques of dealing with people in the office. It introduces the office atmosphere to the secretary and thus prepares them for their professional responsibility.
Includes index.
ne 02/07/2021
Loans
Keywords: Secretaries--office services; Office management